Becoming supernatural : how common people are doing the uncommon - Dispenza, Joe, 1962- (Hay House, Inc., 2017)
"The author ... draws on research conducted at his advanced workshops since 2012 to explore how common people are doing the uncommon to transform themselves and their lives. [This book] marries some of the most profound scientific information with ancient wisdom to show how people like you and me can experience a more mystical life. Readers will learn that we are, quite literally supernatural by nature if given the proper knowledge and instruction, and when we learn how to apply that information through various meditations, we should experience a greater expression of our creative abilities; that we have the capacity to tune in to frequencies beyond our material world and receive more orderly coherent streams of consciousness and energy; that we can intentionally change our brain chemistry to initiate profoundly mystical transcendental experiences; and how, if we do this enough times, we can develop the skill of creating a more efficient, balanced, healthy body, a more unlimited mind, and greater access to the realms of spiritual truth. Topics include: Demystifying the body's 7 energy centers and how you can balance them to heal. How to free yourself from the past by reconditioning your body to a new mind. How you can create reality in the generous present moment by changing your energy. The difference between third-dimension creation and fifth-dimension creation. The secret science of the pineal gland and its role in accessing mystical realms of reality. The distinction between Space-Time vs. Time-Space realities... and much more. Using tools and disciplines ranging from cutting-edge physics to practical exercises such as a walking meditation, Dr. Joe offers nothing less than a program for stepping outside our physical reality and into the quantum field of infinite possibilities"--